EXPLORATION OF PRINGGASELA WOVEN FABRIC AESTHETICS AS AN INSPIRATION FOR NEW CREATION DANCE FLOOR PATTERNS - Nahdlatuzzainiyah, Nahdlatuzzainiyah; Febriana, Widia; Sumadewa, I Nyoman Yoga; Hasbullah, Hasbullah; Sidik, Muhammad Alfian; Buana, Daffa Satya Jaya (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
This study explores the aesthetic elements of Pringgasela woven fabric, a traditional textile from Lombok, Indonesia, as a source of inspiration for innovative dance floor pattern designs. Pringgasela weaving is celebrated for its intricate motifs, harmonious color schemes, and rich cultural symbolism. By analyzing its visual and symbolic characteristics, this research aims to reinterpret traditional textile patterns into dynamic and functional spatial designs suitable for modern performance spaces. The study involves an aesthetic analysis of the fabric's patterns, the extraction of key design elements, and their adaptation into modular dance floor layouts. It emphasizes the importance of preserving cultural heritage through contemporary applications, fostering a dialogue between traditional arts and modern creative industries. The results offer a framework for integrating cultural aesthetics into innovative design, contributing to both cultural preservation and artistic innovation.